A NEW INTERPRETATION OF THE STRUCTURE OF INTERNAL HELLENIDES - Argyriadis, I.; Midoun, M.; Ntontos, P. (Bulletin of the Geological Society of Greece, 2010)
This study is based on some new observations made from Southern and Central Evia, Argolis and North-central part of Pindos. Our observations lead us to adopt a simplified view of the paleogeography of Greek mainland just before the Alpine orogeny. The subsequent varied tectonic units originate mainly from the following paleogeographic areas: • A carbonate Arab-African shelf margin which displays several lateral transitions, ridges and basins. In the Greek mainland this margin is represented by the Preapulian, Ionian, GavrovoTripolis, Parnassos zones, Olympus platform and probably the Kavala and Thassos Marbles. • A transition zone from the shelf units to the Tethys ophiolites (Pindos Zone, Styra, Argolis and Hydra, Eretrias new unit). • Tethys ophiolites, which might represent an “ocean” fault zone or subduction of lithosphere along a weak zone. • An Hercynian continental mass (Servomacedonian).